Diet, Dyslipidemia and Breast Cancer: Macronutrients Imbalance as Dietary Risk of Breast Cancer among the Pakhtun Women of Khyber Pakhtunkhwa, Pakistan - Ayub, Hira; Ghaffar, Fazia (Indus Journal of Bioscience Research, 2025)
Breast cancer (BC) is the most prevalent cancer in women and the second foremost reason for cancer-related deaths in after lung cancer. The current study analyzed dietary intake patterns and health indicators of 328 newly diagnosed breast cancer females of Pathan ethnicity at Peshawar district, KP Pakistan. The objectives were to analyze the dietary macronutrient intake patterns and its subsequent effects on the prevalence of dyslipidemia among these breast cancer patients. Participants, selected from Khyber Teaching Hospital, provided data on demographics, anthropometrics and biochemical tests covered random blood glucose and lipid profile. Key findings include a predominantly married sample (98%), with 18.2% from peri-urban areas and 48.2% having laborer husbands. The majority (76.4%) lived in joint family systems with a monthly income below 30 thousand. The mean BMI was 28.368 ± 4.9890, indicating an overweight tendency. Family history revealed conditions like diabetes, hypertension, elevated blood lipids, obesity, and overweight. Blood test results indicated high cholesterol, triglycerides, HDL, and LDL, suggesting generalized body then contribution to overweight and linked to the disease or diet. This study suggests that total dietary fat and its subtypes may increase the risk of breast cancer among Pathan women. A direct association was found between fat intake and BC development. Cautious fat consumption is recommended to reduce risk. Further research is needed, and nutrition education should be prioritized, especially for Pakhtun women, to promote dietary improvements.